RELATIONSHIP OF SERUM DIPEPTIDYL PEPTIDASE-IV ACTIVITY AND ANTI-CASEIN ANTIBODIES TO GASTROINTESTINAL SYMPTOMS AMONG CHILDREN WITH AUTISM SPECTRUM DISORDER: AN EGYPTIAN STUDY - R El-alameey, Inas; Ahmed, Hanaa H; Eid, Ihab M; El-dory, Ghada; Gameel, Manal (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: The objectives of the study were to assess serum dipeptidyl peptidase-IV (DPP-IV) activity in autistic children suffering from severe gastrointestinal (GI) disorder and to examine the hypothesis that there is a link between DPP-IV activity in serum and GI disorder in a subgroup of children with autism spectrum disorder (ASD). Subjects and Methods: Serum levels of casein antibodies and DPP-IV enzyme activity from 40 autistic children with chronic GI symptoms, and 40 of age-matched children without autism or gastrointestinal (GI) symptoms were assayed using enzyme-linked immunosorbent assay kits. Results: In comparison with controls, developmental milestones were delayed among autistic children. The serum DPP-IV activity was significantly lower in the studied patients (p<0.05), while the mean serum levels of casein antibodies were statistically significantly higher in the studied patients (p<0.01). Multiple logistic regression analysis recorded significant association between the high serum level of antibodies to casein, food selectivity and recurrent attacks of abdominal pain (p<0.05), while the low serum DPP-IV enzyme activity was associated with recurrent attacks of abdominal pain in the studied patients with a prediction of 95% (p<0.05). Conclusions: Serum levels of casein antibodies were higher in children with ASD, and maybe contributes to their abdominal pain, and food selectivity. Serum DPP-IV enzyme activity was lower and associated with recurrent attacks of abdominal pain in the studied patients. They may benefit from a supplemental digestive enzyme formula.